2005
DOI: 10.1002/ajim.20166
|View full text |Cite
|
Sign up to set email alerts
|

Awkward work postures: Association with occupational gender segregation

Abstract: The findings have implications for prevention as well as for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…It has been suggested that females more often than males are employed in occupations with higher risk (Leijon et al 2005). However, when accounting for occupational class, the excess morbidity among females remains the same (de Zwart et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that females more often than males are employed in occupations with higher risk (Leijon et al 2005). However, when accounting for occupational class, the excess morbidity among females remains the same (de Zwart et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…To (Juul-Kristensen et al, 2001;Leijon et al, 2005), although some studies first mount the LT INC on a plastic plate (55 Â 27 mm) before affixing the plate to the arm (Hansson et al, 2006). This placement is hence referred to as the 'caudal' mounting position (Ca-LT) e Fig.…”
Section: Instrumentationmentioning
confidence: 99%
“…INC data recorded during this reference trial were defined to represent 0 elevation (Bernmark and Wiktorin, 2002;Hansson et al, 2006;Leijon et al, 2005).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a substantial body of literature on the importance of social factors in the workplace for health outcomes [Bellaby, 1990;Dwyer and Raftery, 1991;Eakin and MacEachen, 1998], notably with regard to gender [Punnett and Bergqvist, 1999;Messing et al, 2003;Bond et al, 2004;Leijon et al, 2005;Messing and Stellman, 2006;Breslin et al, 2007;Messing and Silverstein, 2009], occupational epidemiologists do not commonly consider that social relations between workers may underlie associations between personal attributes injury outcomes. The social network perspective [Burt, 1982] suggests this notion is worth exploring as many outcomes have been shown to be associated with one's pattern of relations with other group members [Wellman and Berkowitz, 1988;Wasserman and Galaskiewicz, 1994].…”
Section: Introductionmentioning
confidence: 99%